MODERN APPROACHES TO ORGANIZATION EXTRACURRICULAR WORK OF STUDENTS IN HIGHER SCHOOL (Pedagogy of Higher and Secondary Education, 2008)
Іп given article the maintenance and modem approaches to the organization of the out-of-class work, directed on search activity of students and realization of Creative potential reveals.